2007
DOI: 10.1136/bjsm.2006.034041
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for serum creatine kinase in athletes

Abstract: Background: The serum concentration of creatine kinase (CK) is used widely as an index of skeletal muscle fibre damage in sport and exercise. Since athletes have higher CK values than non-athletes, comparing the values of athletes to the normal values established in non-athletes is pointless. The purpose of this study was to introduce reference intervals for CK in athletes. Method: CK was assayed in serum samples from 483 male athletes and 245 female athletes, aged 7-44. Samples had been obtained throughout th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
169
2
34

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(225 citation statements)
references
References 27 publications
20
169
2
34
Order By: Relevance
“…It is possible that due to the high frequency of matches and inadequate recovery soccer players can have consistently elevated CK, which was confi rmed in one study (Heisterberg et al, 2013 ). Our data show much higher values compared to the upper reference value (270 UI/L), for the general population (Mougios, 2007). Furthermore, the high variability of the measure of CK activity must also be taken into account (Halson, 2014), which was the case in this study.…”
Section: Discussionmentioning
confidence: 66%
“…It is possible that due to the high frequency of matches and inadequate recovery soccer players can have consistently elevated CK, which was confi rmed in one study (Heisterberg et al, 2013 ). Our data show much higher values compared to the upper reference value (270 UI/L), for the general population (Mougios, 2007). Furthermore, the high variability of the measure of CK activity must also be taken into account (Halson, 2014), which was the case in this study.…”
Section: Discussionmentioning
confidence: 66%
“…The CK concentration of 14 soccer players remained below the threshold value for the increased risk of injury suggested by Mougios 13 (1492 U/L) and Lazarim et al 10 (975 U/L). It should be noted that the CK concentration of three soccer players was above 975 U/L and the highest being above 1492 U/L, but no clinical problems were reported.…”
Section: Discussionmentioning
confidence: 89%
“…While some studies reported no changes in CK concentration 9,12 others showed CK concentration decreases during a competition 10 . In addition, the absolute values of CK concentration have been used in some of the previous studies which evaluated CK concentration of soccer players 1,9,10,13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values correspond to the normal daily physical demand of soccer players throughout a season, but they are considered high for nonathletes, as studied by Mougios 29 .…”
Section: Discussionmentioning
confidence: 99%